2013
DOI: 10.1111/ene.12119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and MRI predictors of response to interferon‐beta and glatiramer acetate in relapsing–remitting multiple sclerosis patients

Abstract: A lower baseline MRI and clinical activity have been identified as predictors of DMT efficacy in patients with RRMS in routine clinical practice. Evaluation of clinical and MRI activity at 1 year is recommended to monitor patients over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
2
24
2
Order By: Relevance
“…58 Statements and recommendations ■ T2 weighted and contrast enhanced T1 weighted brain MRI are the modalities of choice for MS disease monitoring, revealing acute and active inflammation, and clinically silent disease progression 24 Early prediction Some evidence suggests that certain baseline demo graphic variables (for example, age at treatment initi ation), clinical factors (including disease duration at treatment initiation and pretreatment relapse rate) and MRI measures related to disease activity (such as base line lesion load) can help to indicate which patients will benefit most from a first line DMD, and who will have a poor response. 66,[71][72][73][74] However, the relevant studies mainly analysed cohorts receiving different IFN β formulations, produced preliminary or inconsistent results, and have failed to satisfactorily predict treatment response in clinical practice. 70 Other MRI derived metrics-such as global or regional brain volume, or the number of spinal cord lesions-have shown value for predicting relapses or disability progression, 35-37,39,75-77 but have not been specifically analysed for treatment response predictions.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…58 Statements and recommendations ■ T2 weighted and contrast enhanced T1 weighted brain MRI are the modalities of choice for MS disease monitoring, revealing acute and active inflammation, and clinically silent disease progression 24 Early prediction Some evidence suggests that certain baseline demo graphic variables (for example, age at treatment initi ation), clinical factors (including disease duration at treatment initiation and pretreatment relapse rate) and MRI measures related to disease activity (such as base line lesion load) can help to indicate which patients will benefit most from a first line DMD, and who will have a poor response. 66,[71][72][73][74] However, the relevant studies mainly analysed cohorts receiving different IFN β formulations, produced preliminary or inconsistent results, and have failed to satisfactorily predict treatment response in clinical practice. 70 Other MRI derived metrics-such as global or regional brain volume, or the number of spinal cord lesions-have shown value for predicting relapses or disability progression, 35-37,39,75-77 but have not been specifically analysed for treatment response predictions.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…In the respective pivotal clinical trials comparing active treatment to placebo, natalizumab monotherapy reduced annualized relapse rate (ARR) by 68% [9][10][11][12][13][14][15][16] compared to an around 30% reduction for IFN-b preparations and GA. Although these trials largely enrolled treatmentnaive patients, they were conducted in different epochs resulting in different absolute ARRs (ranging from 0.73 to 1.28 in the placebo groups).…”
mentioning
confidence: 99%
“…One of these researches, conducted on 272 patients to assess the response to IFN-b and GA, found that older age at diagnosis, lower basal EDSS and less Magnetic resonance imaging (MRI) activity, increased the probability of response to the treatment. 24 On the other hand, other studies do not share these findings. In a big observational study carried out in our country, the researchers did not find any epidemiological variable (sex, age at MS onset, duration of MS, and duration of GA treatment), nor clinical factors (number of relapses in the last year, basal EDSS and previous failure of IFN-b) significantly associated with the likelihood of attacks or disability progression.…”
Section: Discussionmentioning
confidence: 93%